Engineering Drawing of Cirebon Gunungan Puppet Shape through Ethnomathematics - Ismail Bambang Subianto; Pandu Pramudita (Gondang: Jurnal Seni dan Budaya, 2023)
Cirebon Gunungan Puppet is one of the gunungan puppet figures that has shape characteristics in the Java region. Gunungan puppet is a puppet figure whose presence is considered important in every puppet show. Therefore, these puppet figures are often reproduced to meet the needs of puppet show. However, knowledge of the gunungan puppet preparation is still limited to traditional knowledge that is less understandable by today's younger generation who need more objective and systematic knowledge. Therefore, this study aims to compose knowledge of gunungan puppet with a focus on composing engineering drawings in the Cirebon gunungan puppet shape through ethnomathematics. The method used in this study is qualitative with an experimental approach. The theory used to support the achievement of this gunungan puppet engineering drawing is ethnomathematics. The composition of the Cirebon gunungan puppet engineering drawings produced three stages, that are the base grid system that determined through ethnomathematical ratio, the contour base that resulting from the arrangement of triangle, circle, and square shape, and the outline shape that resulting from drawing the outline from the geometric shape arrangement to create the Cirebon gunungan puppet shape. The results of this research are expected to be a reference for learning traditional art and design objectively and systematically, especially in the creation of Cirebon mountain puppets.